Flow behavior of polypropylenes with different molecular structures in a coat-hanger die - Grieß, Hans Jürgen; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of the flow behavior of three polypropylene melts with different molecular structures during extrusion through a coat-hanger die is presented. Two linear and one long-chain branched material, rheologically characterized in shear and elongation, were investigated. Using laser-Doppler velocimeter measurements of the velocity profiles across the gap height were performed at five various locations along the die. The uniformity of the velocity distribution along the die has been assessed using the maximum velocities v0 of the corresponding velocity profiles across the gap. The velocity distribution along the die changes with throughput and temperature. Regarding the rheological properties, it was found that the power-law index of the viscosity as a function of shear rate has a decisive influence on the uniformity of flow but that the pronounced strain hardening in elongation typical of the long-chain branched polypropylene is not reflected by the velocity distribution along the die. Copyright © 2012 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up